Calculer et donner le résultat des expressions sous la forme la plus simple.

A= 1/2 + 2/3 + 3/4 + 4/5 + 5/6
B=1/2 - 1/3 - 1/4 - 1/5 - 1/6
C=1/2 - (1/3 + 1/4) - (1/5 + 1/6)

voilas j'ai cela a faire merci de votre aide

2

Réponses

2014-02-22T18:10:43+01:00
A=1/2+2/3+3/4+4/5+5/6
A=30/60+40/60+45/60+48/60+50/60
A=213/60 ou 71/20

B=1/2-1/3-1/4-1/5-1/6
B=30/60-20/60-15/60-12/60-10/60
B=-27/60 ou -9/20

C=1/2-(1/3+1/4)-(1/5+1/6)
C=1/2-(4/12+3/12)-(6/30+5/30)
C=1/2-7/12-11/30
C=30/60-35/60-22/60
C=-27/60 ou -9/20
2014-02-22T18:14:02+01:00
A= 1/2 + 2/3 + 3/4 + 4/5 + 5/6
A= 3/6 + 4/6 + 3/4 + 4/5 + 5/6 
A= 12/6 + 3/4 + 4/5
A= 12/6 + 15/20 + 16/20
A= 12/6 + 31/20
A= 120/60 + 93/60
A = 213/60